2014
DOI: 10.1007/s00421-014-2996-5
|View full text |Cite
|
Sign up to set email alerts
|

Greater autonomic modulation during post-exercise hypotension following high-intensity interval exercise in endurance-trained men and women

Abstract: These results characterize greater depressions in cardiovagal baroreflex function, and increased sympathetic activity, following vigorous exercise in endurance-trained individuals compared with normally active participants. This heightened sympathovagal balance after high-intensity exercise may be a compensatory mechanism in response to greater peripheral blood flow demands following vigorous exercise.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
10
1
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 54 publications
5
10
1
3
Order By: Relevance
“…Previous studies (Chan and Burns 2013;Ciolac et al 2010;Cote et al 2014;Liu et al 2012;Nybo et al 2010;Rossow et al 2010) have used similar intensity of training and have found significant reductions in BP following highintensity training, but unfortunately they did not include a detraining component to compare the current results with. Thus, to our knowledge, this is the first study to describe the training and detraining effects of a short-term HIIT intervention.…”
Section: Discussioncontrasting
confidence: 45%
“…Previous studies (Chan and Burns 2013;Ciolac et al 2010;Cote et al 2014;Liu et al 2012;Nybo et al 2010;Rossow et al 2010) have used similar intensity of training and have found significant reductions in BP following highintensity training, but unfortunately they did not include a detraining component to compare the current results with. Thus, to our knowledge, this is the first study to describe the training and detraining effects of a short-term HIIT intervention.…”
Section: Discussioncontrasting
confidence: 45%
“…In order to compare the amount of post-exercise reduction of blood pressure between the participants and to relate it to plasma lipid levels, the blood pressure 30 min after cessation of exercise (mean of measurements at 30, 35 and 40 min after exercise) was defined as parameter for PEH. This time point has been repeatedly reported for the strongest blood pressure regulations after exercise [33][34][35] and showed significant decreases of systolic blood pressure in our study.…”
Section: Statisticssupporting
confidence: 85%
“…It cannot be assumed that these results apply to females even within the follicular phase, because of the numerous effects of estrogen and progesterone on central and peripheral (renal and vascular) mechanisms of fluid regulation, and on net effects of oxidative stress, for example. Studies that have compared effects of Intervals and/or Endurance exercise in females and males have found no difference in the net PEH in fit individuals, although underlying causation may differ between sexes (Rossow et al, 2010 ; Cote et al, 2015 ). Furthermore, the current findings indicate the involvement of the central nervous, anti-diuretic and renin angiotensin systems in the PEH response without the direct measurements of these.…”
Section: Discussionmentioning
confidence: 99%